Customizability of visualizations in web-based learning systems - Díaz, Francisco Javier (2000)
In this article, we discuss the usability and customizability issues of interactive animations and simulations in web-based learning systems. The approach presented here extended our component-based architecture to build up interactive multimedia visualization units by the use of metadata.